Learning analytics, using questionnaires as an activity in an online course, and its pedagogical actions - López Fernández, Raúl (2023)
This work aims to analyze learning analytics, using questionnaires, to complement pedagogical actions for students' growth. The methodology employed was quantitative, drawing from the descriptive branch the statistics of central tendency and dispersion, as well as Violin and inferential graphs, and comparative tests. Regarding key results, there was a significant difference between the measurements under analysis, where the mean increased, first, pairwise, and then among the three as a whole. Students increased their motivation as the course progressed, and from a metacognitive perspective, they consciously and creatively adjusted their self-assessment.